Analysis of TP53 gene expression and p53 level of human hypopharyngeal FaDu (HTB-43) head and neck cancer cell line after microRNA-181a inhibition - Cheah, Yoke Kqueen; Cheng, Ri Wen; Yeap, Swee Keong; Khoo, Chai Hoon; See, H. S. (Fundacao de Pesquisas Cientificas de Ribeirao Preto, 2014)
The identification of new biomarkers for early detection of highly recurrent head and neck cancer is urgently needed. MicroRNAs (miRNAs) are small and non-coding RNAs that regulate cancer-related gene expression, such as tumor protein 53 (TP53) gene expression. This study was carried out to analyze TP53 gene expression using real-time PCR and to determine changes in intracellular p53 level by flow cytometry after downregulation of miRNA-181a miRNA inhibitor in the FaDu cell line. TP53 gene expression showed a 3-fold increment and the p53 protein level was also increased in the miRNA-181a-treated cells. In conclusion, miRNA-181a binds to the TP53 gene and inhibits its expression, decreasing the synthesis of p53.